Studying Children’s Eating at Home: Using Synchronous Videoconference Sessions to Adapt to COVID-19 and Beyond - Venkatesh, Shruthi; DeJesus, Jasmine M. (Frontiers in Psychology, 2021)
The COVID-19 pandemic has disrupted many facets of developmental research, including research that measures children’s eating behavior. Here, children’s food intake is often measured by weighing foods that children are offered before and after in-person testing sessions. Many studies also examine children’s food ratings (the extent to which they like or dislike a food), assessed via picture categorization tasks or hedonic scales. This paper reviews existing research on different methods for characterizing children’s eating behavior (with a focus on food intake, preferences, and concepts) and presents a feasibility study that examined whether children’s eating behaviors at home (including their food intake and ratings) can be measured via live video-chat sessions. The feasibility analyses revealed that an observational feeding paradigm at home yielded a majority (more than 70%) of video-chat recordings that had a sufficient view of the child and adequate sound and picture quality required for observational coding for the majority of the session’s duration. Such positioning would enable behavioral coding of child food intake, parent food talk, and meal characteristics. Moreover, children were able to answer questions to stories and express their preferences via researcher screen-share methods (which can assess children’s self-reported food preferences and beliefs) with low rates of exclusion across studies. The article ends with a discussion on the opportunities and challenges of using online platforms to conduct studies on children’s eating behaviors in their home environments during the COVID-19 pandemic and beyond.